A stochastic reconstruction framework for analysis of water resource system vulnerability to climate‐induced changes in river flow regime. Issue 1 (24th January 2013) - Nazemi, Alireza; Wheater, Howard S.; Chun, Kwok P.; Elshorbagy, Amin
Key Points Climate change causes shifts in flow regime The shifts can be reconstructed Canadian prairies is vulnerable to the regime shifts